A Study on the Experience of Hydrogen Energy Research and Development in Suzhou City - Cheng, Xiaorong (International Journal of Global Economics and Management, 2024)
Through the exploration of advanced models of the hydrogen energy industry both domestically and internationally, it has been found that many developed countries abroad attach great importance to the hydrogen energy industry and provide policies that greatly help the development of the hydrogen energy industry. Whether it is funding, talent, or related supporting laws, they are relatively complete to help enterprises develop hydrogen energy. Beijing, Zhangjiakou, Foshan, and Yunfu cities in China have advanced experience in the construction of hydrogen energy industrial parks. Their park construction not only conforms to local characteristics, but also brings different changes to their surrounding areas, providing favorable assistance for the development and expansion of hydrogen energy.